Caracterización y valoración biogeográfica de los pinares de Pinus uncinata del karst de Larra (Alto Pirineo navarro) para su ordenación y gestión - Lozano Valencia, Pedro José; Cadiñanos Aguirre, José Antonio; Latasa Zeballos, Itxaro; Meaza Rodríguez, Guillermo (Geographicalia, 2014)
This paper has been written within the context of more than 15 years of research work and it is, for now, its last stage. It’s a global landscap evaluation method that focus on vegetation. To date, this methodology has been documented in numerous works (books, articles, chapters in books, documentation and lectures…) and it has been also applied forthe study of some regions of the Iberian Peninsula and Chile. This methodology is now used for the study of Pinus uncinata dominated forest landscape of Larra Karst (navarrese Pyrenees). The aim is to serve as anassessment tool for the diagnosis of the quality of the environment for conservation purposes.
Keywords: Biogeographic valuation; plant landscape; Pinus uncinata; karst of Larra; High Pyrenees of Navarre.